2018
DOI: 10.1016/j.hjc.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus on clinical outcomes and quality of life after transcatheter aortic valve implantation for severe aortic valve stenosis

Abstract: Patients with DM undergoing TAVI demonstrated similar mortality, complication rates, and QoL outcomes compared to patients without DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…On the other hand, several studies have shown similar outcomes in 30-day and follow-up mortality among diabetic and nondiabetic patients, even when subdivided according to the type of DM treatment. 5,12 In our study, we found an increase in medium-term mortality for all causes in the subgroup of patients with insulin-dependent diabetes mellitus, and not in patients with non-insulin-dependent diabetes mellitus. This is in agreement with the findings of the studies of Conrotto et al 11 and Abramowitz et al, 6 which demonstrated a similar association.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…On the other hand, several studies have shown similar outcomes in 30-day and follow-up mortality among diabetic and nondiabetic patients, even when subdivided according to the type of DM treatment. 5,12 In our study, we found an increase in medium-term mortality for all causes in the subgroup of patients with insulin-dependent diabetes mellitus, and not in patients with non-insulin-dependent diabetes mellitus. This is in agreement with the findings of the studies of Conrotto et al 11 and Abramowitz et al, 6 which demonstrated a similar association.…”
Section: Discussioncontrasting
confidence: 38%
“…4 However, evidence of the influence of diabetes on outcomes of patients undergoing TAVI is scarce and contradictory. [5][6][7][8] The objective of this study was to investigate the impact of diabetes on clinical outcomes in the short and medium term in patients with severe aortic stenosis undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this was not reflected in higher mortality rate in DM patients undergoing TAVI. In study by Tokarek et al, 110 DM was not associated with a higher 30-day or 12-month all-cause mortality after TAVI nor was it associated with decreased post-procedural quality of life. A study by Mendez-Bailon et al 111 as well as a meta-analysis by Sun et al 112 did not find that diabetic patients have worse short-term outcome compared to non-diabetic patients when it comes to TAVI versus SAVR, or to TAVI only.…”
Section: Interventional Therapymentioning
confidence: 83%
“…The obese patients had a higher prevalence of comorbidities, including diabetes mellitus [6]. A link between major vascular and bleeding complications and insulin-treated diabetes was reported [24,25]. Improved operator skills and a reduction in sheath and valve sizes may be partially responsible for the decreased rate of vascular complications as compared to previous studies.…”
Section: Discussionmentioning
confidence: 96%